Psychometric Scale of Tax Compliance Potential Clusters of Prospective Taxpayers - Diyah Probowulan; Retno Murwanti (Jurnal Akuntansi dan Perpajakan, 2025)
This study explores the potential for enhancing tax compliance among prospective taxpayers in Indonesia by developing a psychometric scale that measures psychological factors influencing compliance behaviour. The research was conducted at the University of Muhammadiyah Jember with 225 Accounting Study Program students, who were selected purposively because they represent a relevant group of future taxpayers with foundational knowledge of taxation and financial literacy, making them an appropriate context for examining tax compliance potential. Using a quantitative approach and a structured questionnaire, the study measured intelligence, personality, and skills as independent variables, with tax compliance potential (PTC) as the dependent variable. The findings indicate that intelligence and personality do not have a significant effect on tax compliance potential, whereas skills show a strong positive correlation and significant influence, suggesting that practical competencies in tax administration and the use of tax-related technology are crucial for improving compliance among prospective taxpayers. These results are closely linked to contemporary tax compliance issues in Indonesia, where administrative capability and digital literacy are increasingly important in supporting effective tax systems. By situating the research within an educational setting and aligning the methodological choices with the characteristics of the respondents, this study contributes to a deeper understanding of tax compliance behavior through a psychometric framework. It underscores the importance of a holistic approach to tax education that not only considers individual traits but also emphasizes skill development, social norms, and curriculum-based interventions to strengthen future taxpayers’ compliance behavior.